Biocompósitos de amido de milho, bagaço de cana-de-açúcar e cera de carnaúba : produção e caracterização - Gomes, Áleft Verlanger Rocha (2024)
Biodegradable materials have been increasingly refined due to concerns about sustainable development. Some of these materials that have gained prominence are biocomposites, which emerge as an alternative to composites of synthetic polymer matrices, as they can be disposed of without harming the environment. Therefore, the purpose of this study was to obtain biocomposites of corn starch, sugarcane bagasse, carnauba wax, and tween 80 by the casting method, optimizing their properties through the use of a Central Composite Design. Mechanical properties were obtained through tensile tests. Scanning Electron Microscopy was performed on the fractured surfaces of the specimens to explain the interaction between the corn starch matrix and the other components. Biodegradability analysis of the biocomposites was conducted to assess degradation promoted by microorganisms. Moisture sorption isotherms were obtained to evaluate the effect of water on the biocomposites. The color and density of the biocomposites were also analyzed. Significant response surface models for the tensile test properties were obtained through the Central Composite Design. The results highlight the importance of sugarcane bagasse as a reinforcing agent, as well as elucidating the impact of carnauba wax and tween 80 on interfacial bonding and mechanical performance. Response surface analysis offers valuable insights for optimizing biocomposite formulations to meet specific application requirements. Regarding moisture absorption, the results obtained from moisture sorption isotherms reveal that the addition of carnauba wax and sugarcane bagasse reduces water absorption by the biocomposites.